Modelling of friction stir welded AA2139 aluminium alloy panels in tension and blast. (May 2022) - Awang Draup, A.J.; Rodgers, B.; Prangnell, P.B.; Li, Q.M.; Lunt, M.J.; Robson, J.D.
Highlights: A microstructure-property model for FSW aluminum. Predicts strain localization during blast. Abstract: Predicting the performance of welds under blast loading is challenging, particularly in alloys where the weld region is associated with significant material property gradients. This situation arises for friction stir welds of aluminium alloy AA2139, which represents an example case of a high strength aluminium alloy. To address this problem, a novel multiscale model has been developed that captures the effect of welding on the microstructure and links this to the constitutive material behaviour. The properties of the local weld regions are determined by generating equivalent microstructures in specimens of sufficient size to perform representative tensile and high strain rate compression tests. In this way, the local material properties can be obtained based on the fundamental controlling microstructure, independent of the weld configuration. The constitutive behaviour informs a finite-element model at the macro-scale in which material property gradients arising from microstructural changes are captured. The model has been demonstrated to accurately predict the local strain evolution across the weld zone and demonstrates that strain localization occurs in the heat affected zone region for both cross-weld tensile tests and air blast loading. It is shown that the gradual change in strength between weld zones must be correctly accounted for to predict the correct strain localization behaviour. The work highlights the importance of an accurate description of the variation in local material properties in determining the response of structures under blast loading.